2021
DOI: 10.3390/ijerph18052488
|View full text |Cite
|
Sign up to set email alerts
|

Moderating Effect of the Power–Distance Belief on the Relationship between Employees’ Service Failures and Customers’ Behavioral Outcomes in the Sport Service Industry

Abstract: This study was designed to examine the moderating effects of the power–distance belief (PDB) on the relationship between employees’ service failures and customers’ transactional and non-transactional outcomes in a fitness center context. To test the relationships among these variables, we employed two pretests and a main experiment. In Pretest 1, a critical incident technique (CIT) was used to identify the employees’ service failure situations in fitness centers. Then, in Pretest 2, we developed two written sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
(122 reference statements)
0
2
0
Order By: Relevance
“…Overall, the combination from the results of the study showed that gym-goers would prefer services that are cost-effective and at the same time have special offers with VIP services, one-on-one training, fully airconditioned, cash or online payment, utilization of swipe/tap login, and with 24 h operation. This shows that to satisfy customers' preferences, comfortability and security should be the priority of fitness centers [68]. Moreover, the satisfaction of gym-goers will promote consumer-employee relationship and will have positive consumer behavior [63].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the combination from the results of the study showed that gym-goers would prefer services that are cost-effective and at the same time have special offers with VIP services, one-on-one training, fully airconditioned, cash or online payment, utilization of swipe/tap login, and with 24 h operation. This shows that to satisfy customers' preferences, comfortability and security should be the priority of fitness centers [68]. Moreover, the satisfaction of gym-goers will promote consumer-employee relationship and will have positive consumer behavior [63].…”
Section: Discussionmentioning
confidence: 99%
“…In a society with high levels of power distance, customers display less tolerant to service employees; they tend more to be angry if employees have less time to serve them (i.e. high job demands) (Song and Byon, 2021). However, in low-power distance contexts, inequality is less tolerated and hierarchy is deemphasized.…”
Section: Potential Moderatorsmentioning
confidence: 99%